The influence of body position on the straddled Tkatchev`s flight phase in men`s horizontal bar - Spencer, K.; Schuhmann, M. (Journal of Human Sport & Exercise, 2017)
To examine the effect of level of expertise on the flight phase of the straddled Tkatchev we analysed six male gymnasts (mass = 64.0 +/- 3.0kg, height = 1.67 +/- 0.06m) split into three proficiency levels Elite, Intermediate and Beginners. The preparation phase, flight phase and re-grip phase were sub-divided into ten steps that focussed on three different angularities (bar, shoulder and torso). Angular dimensions between the shoulder and torso and leg were measured using digitised points at the shoulder, trochanter major and lateral malleolus using Sportscode Elite (V10, Sportstec, Australia). A one-way ANOVA was conducted to determine differences between the groups. The results found different angles and body positions influence the flight phase of the Tkatchev. A late flexion in the downward phase with a straight position at the vertical line below the high bar influences the following movement of the Tkatchev positively. An early-piked position with a late straight/hyperextension upward phase increases the energy of the gymnast to reach a greater height above the bar. Both come with a shorten time of preparing and increased time during flight phase. By staring the preparing phase of Tkatchev before reaching the handstand position the gymnast also shorten the time of the giant swing. But then the athlete has to be faster in each execution for each segment, especially in hip flexion during the countermovement. The best time of re-grasping the bar is with a bonded body position and at an angle degree of 412°